Beta 2-band synchronization during a visual oddball task - Kukleta, Miloslav; Bob, Petr; Brázdil, Milan; Roman, Robert; Rektor, Ivan (Physiological research, 2009)
The study investigated whether specific changes in phase synchrony in the beta 2 frequency band of EEG (25-35 Hz) occurred during a recognition task. The level of synchrony was examined between one hundred and eighty loci in the frontal and temporal lobes of eight epileptic patients with intracerebral electrodes; the EEG records were obtained during a visual oddball task. In each pair of records, the correlation curves were created from the sequence of correlation coefficients calculated. These curves consisted of irregular oscillations between the maximal and minimal r-values. Transient highly synchronized activity was observed during the whole time course of the experiment in all record pairs investigated and a significant relationship was found between the number of such episodes and the mean correlation coefficient (Spearman R 0.84; N 3240; p<0.001). On averaged curves, which were calculated using stimulus onsets as the trigger of averaging, a significant increase of the mean correlation coefficient in the post-stimulus epoch was found (p<0.01 after both target and non-target stimuli; t-test for dependent samples). As the cognitive demand significantly increases after stimulus presentation, the results are considered to be the first evidence from intracranial recording of increased synchronization in the beta 2 frequency band related to the cognitive activity.
Keywords: elektroencefalografie; Humans; zraková percepce; čelní lalok; lidé; financování organizované; Visual Perception; Cortical Synchronization; Financing, Organized; Female; lidé středního věku; Electroencephalography; Electrodes, Implanted; Male; implantované elektrody; Adult; spánkový lalok; dospělí; korová synchronizace; Temporal Lobe; Middle Aged; ženské pohlaví; mužské pohlaví; Frontal Lobe